Effectiveness of chemical pleurodesis in spontaneous pneumothorax recurrence prevention: a systematic review. Issue 12 (1st November 2016) - Hallifax, R J; Yousuf, A; Jones, H E; Corcoran, J P; Psallidas, I; Rahman, N M
Abstract : Objectives: Spontaneous pneumothorax is a common pathology. International guidelines suggest pleurodesis for non-resolving air leak or recurrence prevention at second occurrence. This study comprehensively reviews the existing literature regarding chemical pleurodesis efficacy. Design: We systematically reviewed the literature to identify relevant randomised controlled trials (RCTs), case–control studies and case series. We described the findings of these studies and tabulated relative recurrence rates or ORs (in studies with control groups). Meta-analysis was not performed due to substantial clinical heterogeneity. Results: Of 560 abstracts identified by our search strategy, 50 were included in our systematic review following screening. Recurrence rates in patients with chest tube drainage only were between 26.1% and 50.1%. Thoracoscopic talc poudrage (four studies (n=249)) provided recurrence rates of between 2.5% and 10.2% with the only RCT suggesting an OR of 0.10 compared with drainage alone. In comparison, talc administration during video-assisted thoracic surgery (VATS) from eight studies (n=2324) recurrence was between 0.0% and 3.2%, but the RCT did not demonstrate a significant difference compared with bleb/bullectomy alone. Minocycline appears similarly effective post-VATS (recurrence rates 0.0–2.9%). Prolonged air leak and recurrence prevention using tetracycline via chest drain (n=726) is likely to provide recurrence rates between 13.0% and 33.3% and autologous blood patch pleurodesis (n=270) between 15.6% and 18.2%. Conclusions: Chemical pleurodesis postsurgical treatment or via thoracoscopy appears to be most effective. Evidence for definitive success rates of each agent is limited by the small number of randomised trials or other comparative studies.